(untitled) (Nóema, 2021)
This paper investigates the ecological implications of two different trends in systems science: (1) Ludwig von Bertalanffy’s General Systems Theory (GST), which establishes the framework of Eugene Odum’s Systems Ecology; (2) Second-Order Cybernetics (SOC), a systemic approach outlined by Heinz von Foerster, Humberto Maturana, and Niklas Luhmann, in which the roots of a new ecological paradigm called General Ecology can be found. In the article, GST and SOC will be compared with respect to their different ways of conceiving a system and its genesis; the role of the observer in defining the boundaries of a system; and the relation between system and environment. It will be shown how SOC, contrasting the principle of hierarchical control of GST, leads to the notion of ecological differences, which indicates a plurality of system-environment dyads, problematizing the idea of environment as a physical and objective reference.